2020
DOI: 10.1515/cppm-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of operational and design parameters of a Simultaneous Mixer-Separator for enhanced continuous biodiesel production

Abstract: Nowadays, biodiesel is promoted as an alternative and renewable fuel. The mass-transfer limited transesterification reaction is commonly used for biodiesel production, but it could benefit from process intensification technologies. The Simultaneous Mixer-Separator (SMS) is a novel process intensification reactor capable of integrating the mixing and separation of reactants within a single unit. The current study aims to determine the ideal parameters for continuous biodiesel production using an SMS setup that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Considering that the minimum water to biodiesel ratio required for the biodiesel wet washing using conventional method is 3:1 (V/V %), it is concluded that results obtained in this study can affect the consumed water content for biodiesel wet washing up to 75%. From an economic perspective, the biodiesel producing costs can be reduced, and the production of this fuel can be more costeffective [63]. Also, the values suggested by the software were experimentally tested in the current study, and the obtained 4% difference can validate the predictability power of the model.…”
Section: Optimizationmentioning
confidence: 84%
“…Considering that the minimum water to biodiesel ratio required for the biodiesel wet washing using conventional method is 3:1 (V/V %), it is concluded that results obtained in this study can affect the consumed water content for biodiesel wet washing up to 75%. From an economic perspective, the biodiesel producing costs can be reduced, and the production of this fuel can be more costeffective [63]. Also, the values suggested by the software were experimentally tested in the current study, and the obtained 4% difference can validate the predictability power of the model.…”
Section: Optimizationmentioning
confidence: 84%